Immune response following a two-dose schedule of bivalent HPV vaccination among girls and boys - Middeldorp, Marit; Duijster, Janneke W.; van de Kassteele, Jan; van der Klis, Fiona R.M.; de Melker, Hester E. (Frontiers in Immunology, 2024)
This longitudinal cohort study describes the kinetics in antibody levels after two doses of the bivalent human papillomavirus (HPV) vaccine in girls (birth cohort 2001) vaccinated in the routine Dutch vaccination program at 12 years of age, up to 7.5 years post-vaccination. Also, the antibody response one month post-vaccination of the first cohort of boys (birth cohort 2012, vaccinated at 10 years of age) eligible for HPV vaccination in the Netherlands is presented.Blood samples and questionnaire data were collected of girls and boys. HPV type-specific antibody concentrations (LU/mL) against HPV16/18/31/33/45/52/58 were assessed using a validated virus-like particle (VLP) multiplex immunoassay. For girls, antibody decays over time were modelled using the modified power-law decay model and the exponential decay model.The Geometric Mean Concentrations (GMCs) remained higher for HPV16/18 than for HPV types 31, 33, 45, 52, and 58 among girls up to 7.5 years post-vaccination. The antibody levels of HPV16 and HPV18 reached plateau values of 482 and 159 LU/mL, respectively.Mathematical modelling showed that the half-life values of HPV16/18 were 2.4-to 4.5-fold higher compared with the half-life values of the other HPV types. Among boys (aged 10 years), the GMC for HPV16 was significantly higher than among girls one month post-vaccination (aged 12 years).The GMCs of all HPV types declined over time, although the GMCs of HPV16/18 remained relatively high up to 7.5 years post-vaccination. The GMCs for HPV16/18 among boys were at least equally high as the GMCs among girls at one month post-vaccination. Further followup of the cohort of boys is needed to gain knowledge on long-term immune responses of young boys following bivalent HPV vaccination.